2013
DOI: 10.1523/jneurosci.0896-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Innervation and Recruitment of Different Classes of Motoneurons in Adult Zebrafish

Abstract: In vertebrates, spinal circuits drive rhythmic firing in motoneurons in the appropriate sequence to produce locomotor movements. These circuits become active early during development and mature gradually to acquire the flexibility necessary to accommodate the increased behavioral repertoire of adult animals. The focus here is to elucidate how different pools of motoneurons are organized and recruited and how membrane properties contribute to their mode of operation. For this purpose, we have used the in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(125 citation statements)
references
References 41 publications
(2 reference statements)
4
117
0
1
Order By: Relevance
“…Studies in neonatal rodents have shown that spinal neurons within a neuronal population, or from different neuronal populations, are recruited based on the locomotor frequency (Crone et al 2008(Crone et al , 2009Talpalar et al 2013;Zhong et al 2011). Similar results have been found in nonmammalian vertebrates, such as the zebrafish (Ampatzis et al 2013;Ausborn et al 2012;Gabriel et al 2011;McLean et al 2007McLean et al , 2008McLean and Fetcho 2009).…”
Section: Neural Control Of Interlimb Coordination and Locomotor Speedsupporting
confidence: 87%
“…Studies in neonatal rodents have shown that spinal neurons within a neuronal population, or from different neuronal populations, are recruited based on the locomotor frequency (Crone et al 2008(Crone et al , 2009Talpalar et al 2013;Zhong et al 2011). Similar results have been found in nonmammalian vertebrates, such as the zebrafish (Ampatzis et al 2013;Ausborn et al 2012;Gabriel et al 2011;McLean et al 2007McLean et al , 2008McLean and Fetcho 2009).…”
Section: Neural Control Of Interlimb Coordination and Locomotor Speedsupporting
confidence: 87%
“…Serotonin has been shown to reduce the interbout period, resulting in increased motor output, in active and fictive swimming (Brustein et al, 2003). Work incorporating network rhythmicity and intrinsic properties of motor neurons showed how zebrafish can accomplish increases in swimming frequency using a specific pattern of motor neuron recruitment (Menelaou and McLean, 2012), and this pattern of segregation of motor neuron pool by swimming frequency continues to adult stages (Ampatzis et al, 2013). The behavioral observations we present here are the first case where this broad range of swimming speeds has been experimentally evoked in an intact, non-paralyzed preparation, and this experimental paradigm provides an additional tool to study these CPG mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…These conductances have lower activation thresholds in higher Rin motoneurons than lower ones (Lee and Heckman, 1998, 1999), which reinforce the gradient in intrinsic excitability generated by Rin. In both adult and larval zebrafish, there are also differences in the potential contribution of non-linear membrane properties to motoneuron recruitment (Ampatzis et al, 2013; Menelaou and McLean, 2012). In this sense, the pattern of temporal summation related to membrane time constant we describe here would be enhanced by the non-linear properties of both limb and axial motoneurons.…”
Section: Discussionmentioning
confidence: 99%